The Balance of Human Effort (Istiyar) and God’s Destiny in The Javanese Manuscript of The Serat Piwulang Bêcik of the 20th Century - Nuriya, Nguliyatun; Zulaili , Iin Nur (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the concept of istiyar (human effort) and divine destiny in the Javanese manuscript Serat Piwulang Bêcik by Ki Padmasusastra in the 20th century. In previous research works, the discussion focused more on the Javanese Piwulang manuscript in its normative and social policy aspects, so in this case the researcher will highlight the relationship between istiyar (human effort) and divine decree as a form of balance between this world and the afterlife. The method used in this study is descriptive analysis based on philological data sourced from Serat Piwulang Bêcik which has been digitized and written in Javanese language and script. This study, in addition to using philological data to analyze the text, uses the auxiliary science of hermeneutics from Gadamer to obtain the validity of the research data. From Gadamer’s principles of thought, the researcher adopts the concept of Bildung (self-formation), horizon fusion, and question-and-answer logic as interpreters of moral messages contextually and historically. The three main findings of this study are: First, Serat Piwulang Bêcik presents an implicit critique of the relationship between istiyar (human effort) and divine decree, which is stronger. Second, it highlights a text that indirectly rejects excessive self-materialism without recognizing human limitations. Third, it formulates the concept of balance between istiyar and destiny as the foundation of Javanese character education, emphasizing the obligation to strive and be aware of the divine role in human life. Theoretically, this research contributes to the study of Javanese literary hermeneutics by applying Gadamer’s Bildung concept to the didactic texts of the Indonesian archipelago. Practically, these findings enrich contemporary discussions on character education in Indonesia, addressing the disruptions of globalization by avoiding two extremes: resignation without effort and reliance on one’s own abilities without involving God. This study concludes that Serat Piwulang Bêcik provides an ethical framework based on local Javanese wisdom on how to balance human effort and belief in God.